Analysis of The Curative Effect of Tubularized Incised Plate Urethroplasty for Distal Hypospadias With The Dysplastic Corpus Spongiosum Covering Technique - Ji, Linghua; Chen, Shuqing; Chen, Yuehua; Zhao, Jun; Yin, Qiyou; Xian, Hua; Ge, Wenliang (Urology Journal, 2023)
Purpose: To investigate the use of tubularized incised plate (TIP) urethroplasty for distal second- and third-degree hypospadias to free the dysplastic forked corpus spongiosum and Buck’s fascia, which are used as a covering material for the new urethra, thereby reducing the incidence of urinary fistula and other complications in the coronal sulcus. Materials and Methods: Clinical data of 113 patients with distal hypospadias treated with TIP urethroplasty from January 2017 to December 2020 were retrospectively analyzed. The study group comprised 58 patients (use of dysplastic corpus spongiosum and Buck’s fascia to cover the new urethra), and the control group comprised 55 patients (use of dorsal Dartos fascia to cover the new urethra). Results: All children were followed up for more than 12 months. In the study group, 4 patients developed urinary fistulas, 4 developed a urethral stricture, and no case developed glans fissure. In the control group, 11 patients developed urinary fistulas, 2 developed a urethral stricture, 3 developed a glans cracking. Conclusion: Using the dysplastic corpus spongiosum to cover the new urethra increases the amount of tissue in the coronal sulcus and reduces the incidence of urethral fistula, but it may increase the incidence of urethral stricture.